Ecological Study of Sonamarg: With Special Reference to the Ichthyofauna of River Sindh in Kashmir Himalaya - Gulzar, Aadil; Yaqoob, Sabba; Shah, Uzma Noor (Asian Journal of Biological and Life Sciences)
Brown trout and rainbow trout are the two species which constitute trout fishery in the Indian uploads. In the Himalayan region, Brown trout is the only trout which supports sport fishing while in the southern region rainbow trout is the principal one. The valley of Kashmir abounds number of aquatic resources. Among lotic habitats, the river Jhelum occupies an important place in the valley followed by streams. The major fishery of the river is constituted by the Schizothoracines. The fish fauna of the valley is quite different from the rest of country and is dominated by the important endemic Schizothoracine group. During the present study, a total of 5 species of fish were recorded in maximum number from site III from river Sindh. All the species had a distinct distribution pattern was evident from their occurrence and catches from various sites. Schizthoracines are the most important endemic fish occurring in the Himalayan aquatic habitats
Keywords: Brown trout; Kashmir Himalaya; Lotic habitats; River sindh; Schizothorax